2014
DOI: 10.1155/2014/762986
|View full text |Cite
|
Sign up to set email alerts
|

Physical Performance Is Associated with Working Memory in Older People with Mild to Severe Cognitive Impairment

Abstract: Background. Physical performances and cognition are positively related in cognitively healthy people. The aim of this study was to examine whether physical performances are related to specific cognitive functioning in older people with mild to severe cognitive impairment. Methods. This cross-sectional study included 134 people with a mild to severe cognitive impairment (mean age 82 years). Multiple linear regression was performed, after controlling for covariates and the level of global cognition, with the per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 66 publications
3
9
0
Order By: Relevance
“…15 The current results also complement the findings from Nocera et al's report of improvements in Generativity and cardiorespiratory fitness, following a cycle-based aerobic intervention 24 and Emery et al who found a selective effect of exercise-induced cardiorespiratory fitness on Verbal Generativity in older adults with chronic obstructive pulmonary disease. 25 Similarly, the association between fitness and Updating/Working Memory supports earlier findings from Volkers et al 26 and McAuley et al, 27 who both reported positive associations between fitness and Updating/Working Memory in older adults. The hypothetical link between physical activity, cardiorespiratory fitness, and cognitive function holds that changes in fitness precede changes in cognitive function.…”
Section: Discussionsupporting
confidence: 80%
“…15 The current results also complement the findings from Nocera et al's report of improvements in Generativity and cardiorespiratory fitness, following a cycle-based aerobic intervention 24 and Emery et al who found a selective effect of exercise-induced cardiorespiratory fitness on Verbal Generativity in older adults with chronic obstructive pulmonary disease. 25 Similarly, the association between fitness and Updating/Working Memory supports earlier findings from Volkers et al 26 and McAuley et al, 27 who both reported positive associations between fitness and Updating/Working Memory in older adults. The hypothetical link between physical activity, cardiorespiratory fitness, and cognitive function holds that changes in fitness precede changes in cognitive function.…”
Section: Discussionsupporting
confidence: 80%
“…We did not detect any association of VO 2 max with working memory accuracy on any load. While similar findings of no associations between cardiovascular fitness and working memory have been previously reported in middle-aged Swedish office workers 84 , several studies have pointed toward a positive association between VO 2 max and working memory performance, at least in healthy adolescents and younger adults [85][86][87][88] , and in older adults with mild to moderate cognitive impairment 89 . The absence of clinically evident cognitive impairment in our sample, the level and variability in their fitness levels, and the small sample size may all have contributed to this discrepancy.…”
Section: Discussionsupporting
confidence: 73%
“…The main findings showed that older people with cognitive impairment performed significantly worse on the physical fitness tests CSR, Up&go test and 6-min walk test compared to older people recently discharged from hospital, even when controlling for demographic factors and comorbidity. These results show that being diagnosed with MCI or dementia is associated with lower physical fitness, and support previous studies reporting a strong negative association between cognitive impairment and different aspects of physical fitness [ 22 , 25 , 29 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 ].…”
Section: Discussionsupporting
confidence: 90%